2001
DOI: 10.1046/j.1432-1327.2001.02220.x
|View full text |Cite
|
Sign up to set email alerts
|

Thermal stability of pyrrolidone carboxyl peptidases from the hyperthermophilic Archaeon, Pyrococcus furiosus

Abstract: The temperature adaptation of pyrrolidone carboxyl peptidase (PCP) from a hyperthermophile, Pyrococcus furiosus (Pf PCP), was characterized in the context of an assembly form of the protein which is a homotetramer at neutral pH. The Pf PCP exhibited maximal catalytic activity at 90±95 8C and its activity was higher in the temperature range 30±100 8C than its counterpart from the mesophilic Bacillus amyloliquefaciens (BaPCP). Thermal stability was monitored by differential scanning calorimetry (DSC). Two clearl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 66 publications
1
31
1
Order By: Relevance
“…As revealed by X-ray crystallography and site-directed mutagenesis, a single intersubunit disulfide bridge is responsible for the dimeric nature of Sulfolobus solfataricus glycosyltrehalose trehalohydrolase (118) and pyrrolidone carboxyl peptidase from Thermococcus litoralis (394) and Pyrococcus furiosus (316). Similarly, ferric reductase from Archaeoglobus fulgidus was shown to be a homodimer, with a single disulfide bond serving to link the two subunits of the protein (60).…”
Section: Disulfide Bonds In Cytoplasmic Archaeal Proteinsmentioning
confidence: 99%
“…As revealed by X-ray crystallography and site-directed mutagenesis, a single intersubunit disulfide bridge is responsible for the dimeric nature of Sulfolobus solfataricus glycosyltrehalose trehalohydrolase (118) and pyrrolidone carboxyl peptidase from Thermococcus litoralis (394) and Pyrococcus furiosus (316). Similarly, ferric reductase from Archaeoglobus fulgidus was shown to be a homodimer, with a single disulfide bond serving to link the two subunits of the protein (60).…”
Section: Disulfide Bonds In Cytoplasmic Archaeal Proteinsmentioning
confidence: 99%
“…Previous studies have shown that oligomerization makes a crucial contribution to the stability of proteins [51]. Many archaeal proteins have homo-oligomeric structures, and some reports have shown a correlation between oligomerization and the hyperthermostability of archaeal proteins [52].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, disulfide bonds have been identified in intracellular proteins from other hyperthermophiles, including A. aeolicus (36), Pyrococcus woesei (13), Pyrococcus furiosus (38,39), Thermosphaera aggregans (6), and Thermus thermophilus (25). PyAMase was successfully expressed in E. coli and purified to homogeneity.…”
Section: Discussionmentioning
confidence: 99%